Photophysics and Cell Uptake of Self-Assembled Ru(II)Polypyridyl Vesicles - Finn, Stephen; Byrne, Aisling; Gkika, Karmel S.; Keyes, Tia E. (Frontiers in Chemistry, 2020)
Effective delivery of luminescent probes for cell imaging requires both cell membrane permeation and directing to discrete target organelles. Combined, these requirements can present a significant challenge for metal complex luminophores, that have excellent properties as imaging probes but typically show poor membrane permeability. Here, we report on highly luminescent Ruthenium polypyridyl complexes based on the parent; [Ru(dpp)2(x-ATAP)](PF6)2 structure, where dpp is 4,7-diphenyl-1,10-phenanthroline and x-ATAP is 5-amino-1,10-phenanthroline with pendant alkyl-acetylthio chains of varying length; where x is 6; 5-Amido-1,10-phenanthroline-(6-acetylthio-hexanyl). 8; 5-Amido-1,10-phenanthroline-(8-acetylthio-octanyl). 11; 5-Amido-1,10-phenanthroline-(11-acetylthio-undecanyl); and 16; 5-Amido-1,10-phenanthroline-(16-acetylthio-hexadecanyl). Soluble in organic media, the alkyl-acetylthiolated complexes form nanoaggregates of low polydispersity in aqueous solution. From dynamic light scattering the nanoaggregate diameter was measured as 189 nm and 135 nm for 5 × 10−6 M aqueous solutions of [Ru(dpp)2(N∧N)](PF6)2 with the hexadecanoyl and hexanyl tails respectivly. The nanoaggregate exhibited dual exponential emission decays with kinetics that matched closely those of the [Ru(dpp)2(16-ATAP)]2+ incorporated into the membrane of a DPPC liposome. Cell permeability and distribution of [Ru(dpp)2(11-ATAP)]2+ or [Ru(dpp)2(16-ATAP)]2+ were evaluated in detail in live HeLa and CHO cell lines and it was found from aqueous media, that the nanoaggregate complexes spontaneously cross the membrane of mammalian cells. This process seems, on the basis of temperature dependent studies to be activated. Fluorescence imaging of live cells reveal that the complexes localize highly specifically within organelles and that organelle localization changes dramatically in switching the pendent alkyl chains from C16 to C11 as well as on cell line identity. Our data suggests that building metal complexes capable of self-assembling into nano-dimensional vesicles in this way may be a useful means of promoting cell membrane permeability and driving selective targeting that is facile and relatively low cost compared to use of biomolecular vectors.